A Survey of Reading Comprehension Difficulties for Saudi Students with English Text - Sajid, Muhammad Khalid Mehmood (Journal of American Academic Research, 2015)
The study investigates the reading interest of Saudi students’ reading interests in English, the obstacles hindering their reading efforts, the person who helps them choose their reading materials, the factors that determine their choice of reading materials and the reasons why they read. The statistical analysis of the questionnaire returned by 460 Saudi students revealed that the students have a broad range of reading interests. The top of which are stories, adventure books, books about religion, and magazines about the internet, newspaper world events, publications about innovation in technology, sports magazines, novels, poetry, and plays. On the other hand, they dislike books about economics, sociology, astronomy and mathematics. The findings also showed that the obstacles that hinder their reading efforts are of casual visits to the libraries, inability to get books quickly, non-availability of reading materials, time constraints, lack of local libraries, beliefs of having better things to do than reading. It was also noted that the difficulty of reading materials provided by Department of English Language and Literature, opinions that Reading Comprehension is not as important as improving other language skills were the hindrances that created obstacles for their text comprehension. Moreover, the beliefs that there is no relationship between reading and other language skills, and lack of family interest in reading were also the findings that showed the reading difficulties of Saudi students with English text comprehension. Furthermore, the research revealed that the students choose their reading materials by interest, teacher’s request, the main character, length and literary quality. The studies show that the students read for improving their language, learning something, improving their academic achievements, keeping in touch with the local, economic, cultural, scientific and political developments, improving their local status, keeping in view with what is happening around the world and entertainment. Also, the students depend on themselves, their teachers and their class fellows for choosing their reading materials. Recent studies have shown that there has been a continual decline in the average reading ability among the students studying in the schools, colleges and language centers across Saudi Arabia. The current studies assess Reading Comprehension of English Text of senior Saudi students majoring in English.